Female Theology Meets Poietic Writing: Michela Murgia’s L’incontro (2012) - Heyer-Cáput, Margherita (Quaderni d'Italianistica, 2020)
One of the most acclaimed (female) voices of contemporary Sardinian and Italian literature, Michela Murgia offers in her short novel L’incontro a powerful expression of poietic writing. Writing as poiēsis, as creative force capable of shaping reality through theoretical reflection, expresses itself in the in-between space of literal and metaphorical orders. In particular, L’incontro represents an expression of poietic writing in its combination of female theology and community activism. This contribution reads L’incontro, a novel of formation unfolding along the preparations for the traditional Sardinian Easter ritual of S’incontru, through the lens of feminist theology and within the theoretical framework provided by the theorization of sexual difference. Marina Warner’s (1976) and Virginia Ramsey Mollenkott’s (1983) feminist biblical exegesis, in conversation with the “teologia al femminile” elaborated by Marinella Perroni and Cristina Simonelli, connect Murgia’s L’incontro to her theological essay, Ave Mary: E la Chiesa inventò la donna (2011). In this context Murgia’s writing articulates a concept of poiēsis that intertwines thinking and doing, transcendence and immanence while shaping a more open and inclusive community.